احادیث ِنزو لِ مسیح ابن مریم علیہما السلام میں قادیانیوں کی تاویلات کا تنقیدی جائزہ: A Critical Review of Interpretations of Qādiyānies in Aḥadīth of Nuzūl Al-Masīḥ Ibn e Maryam (علیہما السلام) - Fareed ud din, Hafiz (Al-Amīr Research Journal for Islamic Studies, 2021)
The negation of the crucifixion and murder of Maseeh علیہ السلام and the ascension to heaven are mentioned in the Holy Qur’an and the revelation to the earth is mentioned in the authentic Ahadith. The Holy Qur’an and Hadith do not contradict each other on the ascension and revelation of Maseeh علیہ السلام. Mirza Ghulam Ahmed Qadiyani interpret those thirty verses of the Holy Qur’an are about the death of Maseeh علیہ السلام which have nothing to do with his death. The Hadiths of the revelation of Maseehعلیہ السلام benefit from the Holy Qur’an, not derived from any Ijtihad or Israelism. The word death is not mentioned for Essa علیہ السلام in the Holy Qur’an. It is not possible for the Hadith to describe the return of Essa علیہ السلام to earth before the Day of Judgment and let his death be mentioned in the Holy Qur’an. Otherwise, instead of stating the meaning of Holy Qur’an, the Hadith will contradict the Qur’an. The Qur’an mentions the ascension of Essa علیہ السلام to heaven and the Hadith describes the revelation to the earth. There is not a single Hadith that indicates that Essa علیہ السلام refers to Mirza Ghulam Ahmed of Qadian and his descent means that is born from the mothes’s womb, or it is a descent as buroz (بروزی).